How to improve the quality of care for people on home mechanical ventilation from the perspective of healthcare professionals: a qualitative study - Hanna Klingshirn; Laura Gerken; Katharina Hofmann; Peter Ulrich Heuschmann; Kirsten Haas; Martha Schutzmeier; Lilly Brandstetter; Jutta Ahnert; Thomas Wurmb; Maximilian Kippnich; Bernd Reuschenbach (BMC, 2021)
Abstract Background The rapid increase in the use of home mechanical ventilation (HMV) for people with chronic respiratory failure poses extreme challenges for the healthcare system. People on HMV have complex care needs and require support from an interprofessional team. In Germany, HMV is criticised for inadequate quality standards, particularly in outpatient intensive care practice. The objective of this study was to describe the quality of care for people on outpatient HMV in Germany, Bavaria and provide recommendations for improvement from the perspective of healthcare professionals (HCPs). Methods Semi-structured qualitative telephone interviews with HCPs (i.e., nurses, equipment providers, therapists, and physicians) were analysed using the framework method. The quality framework of Health Improvement Scotland (HIS), which aims to improve the quality of person-centred care, was used to build a deductive analysis matrix. The framework includes the three key areas: (1) Outcomes and impact, (2) Service delivery, and (3) Vision and leadership. The domains (meta-codes) and quality indicators (sub-codes) of the quality framework were used for deductive coding. Results Overall, 87 HCPs (51 female, mean age of 44.3 years, mean professional experience in HMV of 9.4 years) were interviewed (mean duration of 31 min). There was a complex interaction between the existing health care system (Outcomes and impact, 955 meaning units), the delivery of outpatient intensive care (Service delivery, 939 meaning units), and improvement-focused leadership (Vision and leadership, 70 meaning units) that influenced the quality of care for people on HMV. The main barriers were an acceleration in transition management, a neglect of weaning potential, a shortage of qualified professionals and missing quality criteria. The central recommendations for promoting person-centred care were training and supervision of staff and an inspiring leadership. An integrated care structure supporting medical home visits and outpatient rehabilitation should be developed. Conclusion This study describes a heterogeneous and partly deficient care situation for people on HMV, but demonstrates that high quality care is possible if person-centred care is successfully implemented in all areas of service provision. The recommendations of this study could inform the development of a person-centred integrated care structure for people on HMV.